Urinary incontinence - a problem of modern society - Wawryków, Agata; Korabiusz, Katarzyna; Stecko, Monika; Torbe, Andrzej (Journal of Education, Health and Sport, 2018)
Abstract Urinary incontinence is the involuntary leakage of urine through the urethra. The World Health Organization indicates that incontinence is a very important social problem. In addition to a significant deterioration of the quality of life, this ailment significantly affects the social, professional and family life of people suffering from it. Statistics indicate that this problem affects about 5 million people in the Poland, both women and men. There are a number of risk factors, of which the most common are: postpartum period, menopausal period in women, prostatic hypertrophy in men and obesity, severe physical work and smoking in both groups. Physiotherapy is an important element of conservative treatment. The most common therapies are: biofeedback, pelvic floor training and electrostimulation